Comparison of Conversational Corpus and News Corpus on Gender Bias in Indonesian-English Transformer Model Translation - Wijanarko, Andik; Al Haura, Adzkiyatun Nisa; Puspitaningrum, Indar; Saputra, Dhanar Intan Surya (Universitas Bina Darma, 2024)
Gender bias in machine translation is a significant issue that affects text translation and gender perception, often leading to misunderstandings, such as the tendency to default to using male pronouns. For example, the word